Mechanical properties and microstructure evolution of Ti2AlC under compression in 25–1100 °C temperature range. (1st May 2020) - Benitez, R.; Kan, W.H.; Gao, H.; O'Neal, M.; Proust, G.; Srivastava, A.; Radovic, M.
Abstract: This study investigates the effects of the initial grain size and temperature (ranging from room temperature to 1100 °C) on the mechanical properties and microstructure evolution of Ti2 AlC MAX phase. A Hall-Petch like relationship is observed between compressive strength and the grain size below brittle-to-plastic transition temperature (BPTT). However, the compressive strength of fine-grained MAX phase decreases more rapidly with increasing temperature resulting in inverse Hall-Petch effect above BPTT. Results from postmortem EBSD analysis reveal complex microstructural evolution in both fine- and coarse-grained microstructures during loading at different temperatures. The pronounced drop in compressive strength for fine-grained microstructures at temperatures close to BPTT is attributed to creep induced grain boundary sliding resulting in texture development with more grains oriented for easy slip. In coarse-grained microstructures, no significant texture development is observed even though grain refinement occurs at all temperatures. A mathematical model has also been formulated to predict the experimentally observed grain size and temperature dependent variation in the compressive strength of Ti2 AlC over a wide range of grain sizes and test temperatures. The mathematical model accounts for the competing effects of Hall-Petch strengthening and high temperature creep induced softening mechanisms. Graphical abstract: Image, graphical abstract